2016
DOI: 10.18203/2349-3291.ijcp20160137
|View full text |Cite
|
Sign up to set email alerts
|

Study of epidemiological profile, clinico-biochemical spectrum and prognosis of malaria induced renal dysfunction in paediatrics age group

Abstract: INTRODUCTIONMalaria remains a serious health problem in many parts of the world. It causes high morbidity and claims many lives in developing countries each year. Humans are generally infected by four species of malaria parasites. 1Malarial acute kidney injury is commonly found in nonimmune adults and older children with falciparum malaria and occasionally with Plasmodium vivax. Occurrence of malaria induced acute kidney injury in severe falciparum malaria is quite common in Southeast Asia and Indian subcontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
1
Order By: Relevance
“…As per the result of Barsoum RS jaundice is the most common association with malarial ARF (MARF), occurring in more than 75% of cases. 14 As in present study, fever was present in 100% in 124 patients of malaria due to AKI in study done by Naqvi R et al 2003; similarly, 100% patient had fever in a study involving 200 patients by Panwar S et al 15,16 In study by Wasnik PN et al in 80 confirmed cases of Falciparum malaria fever was the most common symptom observed in all patients and majority of patients presented in the hospital within a week of onset of symptoms. 17 AGE patients presented with diarrhoea (75% males and 75% females) vomiting (83.33% males and 75% females), fever (16.67% males only), decreased urine output (100% males and females), pedal oedema (33.33% males and 25% females).…”
Section: Resultssupporting
confidence: 59%
“…As per the result of Barsoum RS jaundice is the most common association with malarial ARF (MARF), occurring in more than 75% of cases. 14 As in present study, fever was present in 100% in 124 patients of malaria due to AKI in study done by Naqvi R et al 2003; similarly, 100% patient had fever in a study involving 200 patients by Panwar S et al 15,16 In study by Wasnik PN et al in 80 confirmed cases of Falciparum malaria fever was the most common symptom observed in all patients and majority of patients presented in the hospital within a week of onset of symptoms. 17 AGE patients presented with diarrhoea (75% males and 75% females) vomiting (83.33% males and 75% females), fever (16.67% males only), decreased urine output (100% males and females), pedal oedema (33.33% males and 25% females).…”
Section: Resultssupporting
confidence: 59%
“…A study by Panwar S et al has observed P. vivax as important cause of nephropathy. 17 But in the present study all oliguric patients were P. falciparum severe malaria cases. Hematuria was a less common (11.1% cases) finding in our study.…”
Section: Outcomecontrasting
confidence: 53%
“…In India, about 70% of the infections reported are due to P. vivax; 25-30% due to P. Falciparum and 4-8% are due to mixed infections. P. malariae is responsible for less than 1% of infections in India [13].…”
Section: Discussionmentioning
confidence: 99%